2018
DOI: 10.3356/jrr-16-104.1
|View full text |Cite
|
Sign up to set email alerts
|

Home Ranges, Habitats, and Roosts of Wintering Burrowing Owls In Agricultural Landscapes In Central Mexico

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To evaluate how long burrowing owls remained at a release site, we recorded the number of minutes between the release when the individual left the site area as determined by radial thresholds of 200, 600, and 1,000 m. We assumed 200 m would capture a burrowing owl's narrower perception of the release environment immediately after release, and 600 m and 1,000 m would capture a broader perception that occur after exploration of the novel environment. We defined the last 2 values based on the central (600 m) and total (1,000 m) home range sizes reported for burrowing owls in several studies (Gervais et al 2003, Moulton et al 2004, Rosenberg and Haley 2004, Valdez‐Gómez et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate how long burrowing owls remained at a release site, we recorded the number of minutes between the release when the individual left the site area as determined by radial thresholds of 200, 600, and 1,000 m. We assumed 200 m would capture a burrowing owl's narrower perception of the release environment immediately after release, and 600 m and 1,000 m would capture a broader perception that occur after exploration of the novel environment. We defined the last 2 values based on the central (600 m) and total (1,000 m) home range sizes reported for burrowing owls in several studies (Gervais et al 2003, Moulton et al 2004, Rosenberg and Haley 2004, Valdez‐Gómez et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…However, in the South America distribution range, the species has colonized urban areas in recent years, reaching higher densities in urban than in rural areas (Rebolo-Ifrán et al 2017;Baladrón et al 2020). Despite observations of burrowing owls foraging in illuminated areas (Griffin et al 2018;Valdez-Gómez et al 2018), ALAN has been overlooked in habitat selection studies (Baladrón et al 2016;Martínez et al 2017;Rebolo-Ifrán et al 2017). ALAN has been considered as a pervasive influence on the habitat use in North America because prey availability may decrease in illuminated areas (Scobie et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We thoroughly searched for owl nests within the study area (~70 hours) and, at each nest found, S1). Since burrowing owls are territorial animals (Green & Anthony 1989, Haug & Oliphant 1990, Gervais et al 2003, Moulton et al 2004, Rosenberg & Haley 2004, Valdez-Gómez et al 2018, Poulin et al 2020, we can ensure that each owl was sampled only once.…”
mentioning
confidence: 99%
“…We tested the influence of habitat suitability on FID considering two spatial scales: burrow adjacency and home range. We used average values of environmental suitability around each burrow (buffer) for a 50m buffer (representing the environmental suitability directly adjacent to the burrow) and a 600m buffer (representing the environmental suitability of the owls' home range - Green & Anthony 1989, Haug & Oliphant 1990, Moulton et al 2004, Rosenberg & Haley 2004, Valdez-Gómez et al 2018, Poulin et al 2020. Each spatial scale buffer was extracted from the suitability raster using the raster package (Hijmans 2017) (Anselin 1995), using the distance matrix as an associated weight (I = -0.063 ± 0.07, P = 0.59) (Gittleman & Kot 1990).…”
mentioning
confidence: 99%